2015
DOI: 10.1080/09205063.2015.1095023
|View full text |Cite
|
Sign up to set email alerts
|

ε-Polylysine and next-generation dendrigraft poly-L-lysine: chemistry, activity, and applications in biopharmaceuticals

Abstract: Polylysine is an important class of polyamino acids with a broad spectrum of applications in biomedical research and development. It can be divided into two classes, α-polylysine and ε-polylysine, the former is synthesized by artificial chemical synthesis and has limited applications due to its high toxicity, and the latter is produced by microbial synthesis as a class of natural polymers and is widely used in various food, medicinal, and electronics products. Another major class of synthetic polymers is dendr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 107 publications
0
30
0
Order By: Relevance
“…Moreover, ε‐PL is not toxic towards humans (Zinoviadou et al ., ). Based on these properties, ε‐PL and its derivatives have a variety of applications in many fields, such as food industries, medicine and pharmaceuticals (Cai et al ., ; Shi et al ., ). However, ε‐PL has poor antioxidant property, which impedes its industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ε‐PL is not toxic towards humans (Zinoviadou et al ., ). Based on these properties, ε‐PL and its derivatives have a variety of applications in many fields, such as food industries, medicine and pharmaceuticals (Cai et al ., ; Shi et al ., ). However, ε‐PL has poor antioxidant property, which impedes its industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Polylysine is a biocompatible, nontoxic polyamino acid with a broad spectrum of usage [20]. PLLs with molecular weights of 15,000-30,000 were usually used in the study of DNA modification, as shorter-chain PLL was shown to have low binding efficiency with DNA [27].…”
Section: Discussionmentioning
confidence: 99%
“…We previously produced a recombination protein of ε immunoglobulin heavy chain fused with PLL selectively targeting the allergen gene to human dendritic cells (DCs) [19]. PLL can electrostatically bind the negatively charged DNA and has extensively been used in drug delivery [20]. Since PLL is not only water soluble and biodegradable but can also prevent conjugated DNA from nuclease degradation and increase the transport efficiency of DNA, it has been shown to be an effective gene vector which makes DNA absorption easy, is presented by APCs, and improves the immunogenicity of DNA vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…There are two kinds of PLL: i.e. α-PLL that is synthesized by artificial means and shows intrinsic toxicity, and ε-PLL that is synthesized using microbial means, having wide application in medicinal, electronics and food [40,41,42,43].…”
Section: Types Of Ph-responsive Polypeptidesmentioning
confidence: 99%